2017
DOI: 10.1002/nme.5561
|View full text |Cite
|
Sign up to set email alerts
|

A computational homogenization approach for limit analysis of heterogeneous materials

Abstract: model together with coupled kinematic and static theorems as well as homogenization theory. Based on finite elements and primal-dual interior point optimization algorithm, the assessment of the macroscopic strength criterion and stability analysis of soils reinforced by stone columns were performed in [9][10][11][12][13]. For periodic plates, a theoretical study on the overall homogenized Love-Kirchhoff strength domain of a rigid perfectly plastic multi-layered plate was reported by [14,15], and numerical dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 48 publications
1
11
0
Order By: Relevance
“…It can be observed that proposed procedure can prove the highly accurate solutions with low computational cost in comparison with approaches presented in [12,16]. The number of variables in present procedure is less than those used in [16], while the numerical result is approximate. Moreover, with the use of cone-based algorithm the resultant optimization problem in present study can be solved rapidly, the CPU-time required for handling the problem is much less than those in [12] using iterative algorithm.…”
Section: Numerical Examplesmentioning
confidence: 80%
See 3 more Smart Citations
“…It can be observed that proposed procedure can prove the highly accurate solutions with low computational cost in comparison with approaches presented in [12,16]. The number of variables in present procedure is less than those used in [16], while the numerical result is approximate. Moreover, with the use of cone-based algorithm the resultant optimization problem in present study can be solved rapidly, the CPU-time required for handling the problem is much less than those in [12] using iterative algorithm.…”
Section: Numerical Examplesmentioning
confidence: 80%
“…Tab. 1 shows present numerical solutions compared with those in [12,16]. It can be observed that proposed procedure can prove the highly accurate solutions with low computational cost in comparison with approaches presented in [12,16].…”
Section: Numerical Examplesmentioning
confidence: 91%
See 2 more Smart Citations
“…Yu [22,23], V.L. Canh et al [24]. Strengths of PRMMC materials are not only affected by the material microstructure, but also by the type of loading they are exerted to.…”
Section: Introductionmentioning
confidence: 99%